The Macroeconomics of Shadow Banking - MOREIRA, ALAN; SAVOV, ALEXI (Journal of Finance, 2017)
ABSTRACT We build a macrofinance model of shadow banking—the transformation of risky assets into securities that are money‐like in quiet times but become illiquid when uncertainty spikes. Shadow banking economizes on scarce collateral, expanding liquidity provision, boosting asset prices and growth, but also building up fragility. A rise in uncertainty raises shadow banking spreads, forcing financial institutions to switch to collateral‐intensive funding. Shadow banking collapses, liquidity provision shrinks, liquidity premia and discount rates rise, asset prices and investment fall. The model generates slow recoveries, collateral runs, and flight‐to‐quality effects, and it sheds light on Large‐Scale Asset Purchases, Operation Twist, and other interventions.